Handgrip strength asymmetry is associated with the risk of neurodegenerative disorders among Chinese older adults. Issue 2 (17th February 2022) - Chen, Zi; Ho, Mandy; Chau, Pui Hing
Abstract: Background: Neurodegenerative disorders, as the irreversible condition, have a long, silent preclinical period. Recognition of early physical signs of neurodegenerative disorders had important practical implications for identifying at‐risk population. The aim of this study was to investigate whether handgrip strength (HGS) asymmetry was associated with the incidence of neurodegenerative disorders among Chinese older adults. Methods: This study used the data of participants aged 60 years and over from three waves (2011–2015) of China Health and Retirement Longitudinal Study. HGS asymmetry was measured with HGS ratio (maximal non‐dominant HGS/maximal dominant HGS), with the value less than 0.9 or more than 1.1 considered as HGS asymmetry. Physician‐diagnosed neurodegenerative disorders were identified by self‐reported or proxy‐reported information. Competing risk analysis was conducted to examine the association between HGS asymmetry and incident neurodegenerative disorders, with mortality treated as the competing event. Results: A total of 4925 participants were included in the analysis [mean (SD) age: 68.1(6.68); female: 49.7%]. Eight hundred and eighty‐eight (18.0%) participants had low HGS and 2227 (45.2%) had HGS asymmetry. During the 4 years of follow‐up, there were 156 cases of neurodegenerative disorders and 422 cases of mortality. The incidence of neurodegenerative disorders was 8.7 per 1000 person‐years [95% confidence interval (CI): 7.4–10.2], and the incidence of mortality was 23.5 per 1000 person‐years (95% CI: 21.4–25.9). Both the cause‐specific model and the Fine–Gray subdistribution hazard model showed that participants with HGS asymmetry had increased hazard of neurodegenerative disorders [hazard ratio (HR) = 1.66, P  = 0.002, 95% CI: 1.202–2.297; subdistribution hazard ratio (SHR) = 1.65, P  = 0.002, 95% CI: 1.202–2.285]. Low HGS, but not HGS asymmetry, was related to the higher hazard of mortality (HR = 1.61, P  < 0.001, 95% CI: 1.297–1.995; SHR = 1.58, P  < 0.001, 95% CI: 1.286–1.951). Conclusions: Handgrip strength asymmetry was associated with the future risk of neurodegenerative disorders among Chinese older adults. Public healthcare providers could consider examining HGS asymmetry along with the maximal HGS as a way to identify those at elevated risk of neurodegenerative disorders.